Peran Hamba Tuhan Dalam Meningkatkan Pertumbuhan Iman Jemaat Di Gksi Elohim Desa Tumbang Koling Kalimantan Tengah - Yosua Gea (Jurnal Kabar Masyarakat, 2024)
This community service is carried out at GKSI Elohim Tumbang Koling Village, which is located in Tumbang Koling Village, Central Kalimantan. The methods used are observation, investigation and study. The implementation of the activity aims to form an understanding of faith in God and at the same time guide the spirituality of the congregation, teenagers and Sunday school children of the Tumbang Koling Village congregation, how important worship fellowship is. The PKM implementation was motivated by the GKSI Elohim congregation not caring enough about worship, this can be seen in the small number of congregations who attend every Sunday service, and often when the service is in progress only a few people participate. In fact, the GKSI Elohim congregation consists of approximately thirty people, members of the congregation and young people. Referring to this problem, this service is therefore present as an alternative form of solving this problem. The ideas offered are: 1) supporting and motivating each other in love. 2). Be diligent and persistent in worship, 3) advise each other to be more active in worship; the solution offered in the book of Hebrews 10:24-25. The results obtained are that the congregation at GKSI Elohim really understands the importance of worship fellowship